Evaluation of the Therapeutic Effect of Traditional Chinese Medicine on Osteoarthritis: A Systematic Review and Meta-Analysis. (14th December 2020) - Wang, Lin; Zhang, Xiao-Fei; Zhang, Xue; Guo, Dong-Yan; Duan, Yu-Wei; Wang, Zhi-Chao; Pei, Li-Shan; Ru, Han; Cheng, Jiang-Xue; Shi, Ya-Jun; Zou, Jun-Bo
Abstract : Background . Osteoarthritis (OA) is a common degenerative disease of bone and joint characterized by the damage of articular cartilage and hypertonia, which often occurs in the middle-aged and elderly. Traditional Chinese medicine (TCM) therapy, including acupuncture (ACU), oral administration, and external use of traditional Chinese medicines (TCMs), can significantly improve the therapeutic effect on OA and reduce the occurrence of side effects. We provide a latest meta-analysis on the treatment of OA with TCM. Materials and Methods . In the electronic database, appropriate articles without language restrictions on keywords were selected until August 1, 2019. All trajectories are screened according to certain criteria. The quality of qualified research was also assessed. We have made a detailed record of the results of the measurement. Meta-analysis was carried out with Revman 5.3 software. Results . Forty-four articles involving 4014 patients (2012 cases in the experimental group and 2002 cases in the control group) with OA were selected. This article focuses on the study of the treatment of OA by using the general mode of TCM. The quality evaluation included in the study was evaluated independently according to the Cochrane intervention system evaluation manual. In this meta-analysis, 68.18% of the literature correctly described the conditions for the generation of random assignment sequences, only 6.82% of the literature correctly mentioned the hidden details of allocation, and all studies mentioned randomly assigned participants. Compared with Western medicine, the total effective rate (TER) of OA treatment in TCM was significantly increased and the recurrence rate (RR) was significantly decreased (P < 0.00001 ). In addition, the experimental group was also superior to the control group in terms of the indicators of joint activity function, inflammatory factor content, and various indicators affecting bone metabolism. It can be showed by the network analysis diagram that Aconiti Radix, Achyranthis Bidentatae Radix, and other TCMs can inhibit inflammatory stimulation and relieve the pain symptoms of patients with OA. ACU at Yinlingquan, Xiyan, and other acupoints can effectively improve the clinical symptoms of patients with OA. Conclusion . TCM therapy in treatment of patients with OA could effectively restore joint function, enhance the TER, and reduce RR. However, the results of this study should be handled with care due to the limitations existing. Some rigorous randomized controlled trials (RCTs) are needed to confirm these findings.